External and internal drivers behind the formation, vegetation succession, and carbon balance of a subarctic fen margin - T. Juselius-Rajamäki; S. Piilo; S. Salminen-Paatero; E. Tuomaala; T. Virtanen; A. Korhola; A. Autio; H. Marttila; P. Ala-Aho; A. Lohila; A. Lohila; M. Väliranta (Biogeosciences)
Peatlands are the most carbon-dense terrestrial ecosystem, and recent studies have shown that the northern peatlands have been (and still are) expanding into new areas. However, depending on the vegetation and hydrological regime in the newly initiated areas, the climate forcing may vary. If these new areas developed as wet fen-type peatlands with high methane emissions, they would initially have a warming effect on the climate. On the other hand, if development began as dry bog-type peatlands, these new peatland areas would likely act as a strong carbon sink from early on. However, although some research has concentrated on the expansion of the new northern peatland areas, there remains a significant lack of studies on the successional development of the newly initiated peatland frontiers. In this research, we combine paleoecological, remote-sensing, and hydrological modeling methods to study the expansion and successional pathway dynamics in a subarctic fen margin in Finnish Lapland and discuss possible implications for the carbon balance of these marginal peatland areas. Our results show that (1) the studied peatland margins started to develop ca. 2000 years ago and have continued to expand thereafter and (2) this expansion has occurred in nonlinear fashion. In addition, wet fen-type vegetation persisted in the studied margin for the majority of the developmental history, and only dryer conditions after the Little Ice Age instigated the fen-to-bog transition. However, a notable part of the fen margins in the Lompolonvuoma and Lompolojänkkä basins has remained wet fen-type vegetation, and the persistence of this vegetation type was likely caused by the hydrological conditions in the peatland and surrounding catchment. Our findings show a large variation in the peatland expansion and succession dynamics, even within a single peatland basin. Although changes in climate conditions initiated the fen-to-bog process in some margins, some vegetation remained in the wet fen stage, showing resilience to allogenic forcings. Thus, when estimating the peatland carbon stocks and predicting the future trajectories for peatland development, this heterogeneity should be taken into account to avoid errors caused by the oversimplification of peatland lateral expansion dynamics.